2018
DOI: 10.1128/aac.01970-17
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ceftolozane-Tazobactam against Carbapenem-Resistant, Non-Carbapenemase-Producing Pseudomonas aeruginosa and Associated Resistance Mechanisms

Abstract: Although carbapenems are effective for treating serious multidrug-resistant infections, carbapenem-resistant (CRPA) is now being reported worldwide. Ceftolozane-tazobactam (C/T) demonstrates activity against many multidrug-resistant isolates. We evaluated the activity of C/T and compared its activity to that of ceftazidime-avibactam (C/A) using a well-characterized collection of non-carbapenemase-producing CRPA isolates. Forty-two non-carbapenemase-producing CRPA isolates from a previous study (J. Y. Lee and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Giddins identified CAZ/AVI resistance in the newly emerging K. pneumoniae ST307 clonal background after only 12 days of CAZ/AVI exposure, with the induction of a 532G-T mutation in the bla KPC-2 gene leading to a D179Y protein substitution as the putative initial mechanism of CAZ/AVI resistance 31. The characterization of some CAZ/AVI-resistant Pseudomonas aeruginosa isolates demonstrated that the entry of CAZ/AVI into the periplasmic space depended on outer membrane permeability 32. Also, the patients infected with KPC2-producing CRE had no previous exposure to CAZ/AVI, but instead had frequent previous exposures to meropenem and cefepime.…”
Section: Discussionmentioning
confidence: 99%
“…Giddins identified CAZ/AVI resistance in the newly emerging K. pneumoniae ST307 clonal background after only 12 days of CAZ/AVI exposure, with the induction of a 532G-T mutation in the bla KPC-2 gene leading to a D179Y protein substitution as the putative initial mechanism of CAZ/AVI resistance 31. The characterization of some CAZ/AVI-resistant Pseudomonas aeruginosa isolates demonstrated that the entry of CAZ/AVI into the periplasmic space depended on outer membrane permeability 32. Also, the patients infected with KPC2-producing CRE had no previous exposure to CAZ/AVI, but instead had frequent previous exposures to meropenem and cefepime.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of carbapenem-resistant P. aeruginosa strains are susceptible to ceftazidime-avibactam [47]. Nonetheless, susceptibility of P. aeruginosa strains to ceftazidime-avibactam depends on the coexistence of various resistance mechanisms affecting porin channel function, efflux pump expression, and/or β-lactamase enzyme expression [48–50]. Ceftazidime-avibactam is not active against A. baumannii or S. maltophilia .…”
Section: Approach To Therapy Of Carbapenem-resistant Gram-negative Inmentioning
confidence: 99%
“…The rise of multidrug-resistant (MDR) Pseudomonas aeruginosa threatens the use of available antibiotics, including carbapenems [1, 2]. The new cephalosporin/ β -lactamase inhibitor combination ceftolozane/tazobactam (C/T) has provided a viable alternative for treatment of infections due to MDR P. aeruginosa [1, 2]. Indeed, many reports have confirmed the success of C/T to combat these organisms [3, 4].…”
Section: Introductionmentioning
confidence: 99%